Porous Covalent Organic Framework Based Hydrogen‐Bond Nanotrap for the Precise Recognition and Separation of Gold. Issue 17 (16th March 2023) - Qiu, Jikuan; Xu, Chang; Xu, Xianhui; Zhao, Yingjie; Zhao, Yang; Zhao, Yuling; Wang, Jianji
Abstract: Utilizing weak interactions to effectively recover and separate precious metals in solution is of great importance but the practice remains a challenge. Herein, we report a novel strategy to achieve precise recognition and separation of gold by regulating the hydrogen‐bond (H‐bond) nanotrap within the pore of covalent organic frameworks (COFs). It is found that both COF‐HNU25 and COF‐HNU26 can efficiently capture Au III with fast kinetics, high selectivity, and uptake capacity. In particular, the COF‐HNU25 with the high density of H‐bond nanotraps exhibits an excellent gold uptake capacity of 1725 mg g −1, which is significantly higher than that (219 mg g −1 ) of its isostructural COF (COF‐42) without H‐bond nanostrap in the pores. Importantly, the uptake capacity is strongly correlated to the number of H‐bonds between phenolic OH in the COF and [AuCl4 ] − in water, and multiple H‐bond interactions are the key driving force for the excellent gold recovery and reusability of the adsorbent. Abstract : Gold recovery with exceptional uptake capacity, high selectivity, and excellent recyclability has been achieved in covalent organic frameworks (COFs) through the regulation of hydrogen‐bond nanotraps within the pore surfaces.